The given system of equations is :
y=2x+14 ...(1)
−4x−y=4 ... (2)
We can solve the above system of equation by method of substitution. Frm equation (1) we have y=2x+14. So, first step is to substitute 2x+14 for y in equation (2). Hence,
-4x - (2x + 14) = 4
-4x - 2x - 14 = 4
- 6x -14 = 4 By combining the like terms.
-6x - 14 + 14 = 4 + 14 Add 14 to each sides of the equation.
- 6x = 18
Divide each sides -6.
x = -3.
Next step is to plug in x=-3 in equation (1) to get the value of y. Therefore,
y = 2(-3) + 14
= -6 +14
= 8
So, y=8.